Women in the Boardroom: How Do Female Directors of Corporate Boards Perceive Boardroom Dynamics? - Mathisen, Gro Ellen (Journal of business ethics, 2013)
This study investigated how female directors of corporate boards of directors (BoD) experience boardroom dynamics. The study represents an initial research trend that moves from a unilateral focus on financial outcomes of female representation in BoDs toward stronger attention on the social dynamics in the boardroom. Drawing on social identity theory, the study proposed that female directors often constitute an out-group within the BoD, preventing them from experiencing positive board dynamics. More specifically, the study explored the extent to which female directors do experience less justice, lower cohesion, and higher levels of conflicts within the BoD than their male counterparts do. Moreover, we assumed that female directors with nontraditional educational backgrounds would be particularly likely to experience negative boardroom dynamics whereas female chairpersons of BoDs would perceive boardroom dynamics more positively than other female directors. The sample consisted of 491 directors from 149 BoDs. Our findings revealed that there were generally few differences in the way female and male directors experienced boardroom dynamics and female chairpersons of BoDs did not perceive the dynamics differently than other female directors. Female directors with nontraditional educational backgrounds perceived the boardroom dynamics somewhat more negatively than other female directors, but the differences were not statistically significant. The conclusions from this study are that there are reasons to believe that female directors are welcomed into boardrooms, not perceived as out-groups, and BoDs are able to benefit from the female directors’ experience and skills.